(untitled) (Research, Society and Development, 2020)
The article aims to reflect on human rights, fundamentals and personality, in order to trace its relationship with the right to access to justice in the exercise of jus postulandi and its effectiveness. For the accomplishment of this work, the hypothetical deductive method approach was used, with bibliographic research in books, periodical publications, scientific articles, printed, national and international legislation. In the end it was concluded that the jus postulandi presents weaknesses that obstruct access to just justice. Also, the performance of the lawyer is essential for the realization of these rights, as well as the dignity of the human person.